Oralność w oryginale i przekładzie portugalskojęzycznej literatury afrykańskiej — przejawy i funkcje - Kruk, Agnieszka (Zagadnienia Rodzajów Literackich, 2022)
Postcolonial African literatures written in Portuguese build their identity by modifying existing linguistic and literary norms. One of its manifestations is including in writings elements of traditional orality. The orality becomes an indicator of identity, it differentiates literatures of colonies and ex-colonies from the one written in the metropolis, it allows to preserve and transmit popular wisdom and references to traditional forms. Although oral elements are an important part of the original, as they create a separate literary style and genre, they are often neutralized in translation. This unfavourable tendency may be the result of an unawareness regarding the importance of orality, lack of sensitivity and an attempt to adjust the translated text to the norms of the target literature. This work aims to gather and analyse different indicators of orality in African literatures written in Portuguese, to examine if and how they are transmitted in Polish translations. To do so, we follow the division of manifestations of orality elaborated by Walter Ong. The awareness of the role played by orality in the analysed texts and sensitivity to its indicators in the texts will allow translators to more consciously choose the strategies and techniques which enable them to show the original’s diversity to target recipients.